Significance of the d-Serine-deaminase and d-Serine metabolism of staphylococcus saprophyticus for virulence - Kline, Kimberly A. (2015)
Staphylococcus saprophyticus is the only species of Staphylococcus that is typically uropathogenic and possesses a gene coding for a D-serine-deaminase (DsdA). As D-serine is prevalent in urine and toxic or bacteriostatic to many bacteria, it is not surprising that the D-serine-deaminase gene is found in the genome of uropathogens. It has been suggested that D-serine-deaminase or the ability to respond to or to metabolize D-serine is important for virulence. For uropathogenic Escherichia coli (UPEC), a high intracellular D-serine concentration affects expression of virulence factors. S. saprophyticus is able to grow in the presence of high D-serine concentrations; however, its D-serine metabolism has not been described. The activity of the D-serine-deaminase was verified by analyzing the formation of pyruvate from D-serine in different strains with and without D-serine-deaminase. Cocultivation experiments were performed to show that D-serine-deaminase confers a growth advantage to S. saprophyticus in the presence of D-serine. Furthermore, in vivo coinfection experiments showed a disadvantage for the ΔdsdA mutant during urinary tract infection. Expression analysis of known virulence factors by reverse transcription-quantitative PCR (RT-qPCR) showed that the surface-associated lipase Ssp is upregulated in the presence of D-serine. In addition, we show that S. saprophyticus is able to use D-serine as the sole carbon source, but interestingly, D-serine had a negative effect on growth when glucose was also present. Taken together, D-serine metabolism is associated with virulence in S. saprophyticus, as at least one known virulence factor is upregulated in the presence of D-serine and a ΔdsdA mutant was attenuated in virulence murine model of urinary tract infection.